Climate change and DIY urbanism in Luanda and Maputo: new urban strategies?. Issue 3 (2nd September 2019) - Udelsmann Rodrigues, Cristina
ABSTRACT: Climate-related phenomena historically have had an impact on the lives of urban dwellers of Luanda and Maputo. Recently, however, urban expansion and congestion of different sorts, aggravated by climate change impacts, call for renewed responses on the part of residents. Rising sea levels and harder impacts of flooding are the most disturbing issues in the two coastal capitals, demanding both institutional responses and strategies of urban residents, particularly the most vulnerable. Based on qualitative data collected in Luanda and Maputo, this article describes how urban residents aim to mitigate and adapt to the effects of climate change and by doing so, shape the cities they live in and their environment.